Meta Analisis Penerapan Media Perangkat Lunak Proteus Dalam Pembelajaran Fisika - Sohibul Akbar; Jhelang Annovasho; Mardaya Mardaya (Lembaga Bale Literasi, 2023)
Understanding physics concepts often faces difficulties due to the lack of resources that can encourage students in learning and improve their understanding. One solution is to use Proteus software as physics learning media. The purpose of this meta-analysis is to evaluate the effect of using Proteus software media in physics learning. This meta-analysis research method involves several stages, such as formulating the research problem, collecting data from various studies, coding the data, and analyzing and interpreting the data. In the journal search, 36 articles were found that discussed the application of Proteus software media in physics learning. There are 6 articles that are relevant to the research conducted. In this article shows that there is a strong influence of the application of proteus software media in learning physics. in this study revealed that the results of the calculation of the effect size of the application of proteus software media in learning physics is 1.55 which is classified as high at 94%. This shows that proteus software media has a high influence in learning physics, especially at the SMA / SMK / MA education level.